The first documented breeding record of White-tailed Lapwing Vanellus leucurus (Lichtenstein, 1823) in Georgia - Budagashvili, Nika; Turkalj, Josip (Pensoft Publishers, 2024)
This paper reports the first documented breeding record of the White-tailed Lapwing Vanellus leucurus in Georgia, with additional information on its status in Georgia and in the adjacent countries.